A Sociolinguistic Study of Code-Mixing on Boy William’s YouTube Channel - Putu Eka Kharisma Dewi; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon (LPPM Universitas Dhyana Pura, 2023)
Language functions as a structured system of conventional vocal symbols utilized for communication. Human beings, being inherently social, reside within communities that are defined by language, culture, and traditions. In contemporary times, many individuals employ multiple languages for communicating with those around them. Sociolinguistics delves into the intersection of language and society, investigating the intricate relationship between the two. An intriguing sociolinguistic phenomenon observed within societies is bilingualism or multilingualism, which signifies proficiency in more than one language by an individual. The objective of this study is to elucidate the patterns, categories, and underlying reasons for code-mixing found in Boy William's YouTube channel. Employing a descriptive qualitative approach, the researchers employed techniques like active listening and note-taking to gather the necessary data. The results reveal that, within a 4.50-minute duration of Boy William's YouTube content, numerous instances of code-mixing manifest in the conversations taking place. It is evident through a comprehensive data analysis, which all point to the code-mixing presence.